Loss of Functional Beta(2)-Microglobulin in Metastatic Melanomas From Five Patients Receiving Immunotherapy - Restifo, Nicholas P. (1996)
BACKGROUND: In a subset of patients with metastatic melanoma, T lymphocytes bearing the cell-surface marker CD8 (CD8(+) T cells) can cause the regression of even large tumors. These antitumor CD8(+) T cells recognize peptide antigens presented on the surface of tumor cells by major histocompatibility complex (MHC) class I molecules. The MHC class I molecule is a heterodimer composed of an integral membrane glycoprotein designated the α chain and a noncovalently associated, soluble protein called beta(2)-microglobulin (β(2)m). Loss of β(2)m generally eliminates antigen recognition by antitumor CD8+ T cells. PURPOSE: We studied the loss of β(2)m as a potential means of tumor escape from immune recognition in a cohort of patients receiving immunotherapy. METHODS: We successfully grew 13 independent tumor cell cultures from tumor specimens obtained from 13 patients in a cohort of 40 consecutive patients undergoing immunotherapy for metastatic melanoma and for whom tumor specimens were available. These cell lines, as well as another melanoma cell line (called 1074mel) that had been derived from tumor obtained from a patient in a cytokine–gene therapy study, were characterized in vitro cytofluorometrically for MHC class I expression and by northern and western blot analyses for messenger RNA (mRNA) and protein expression, respectively, and ex vivo by immunohistochemistry. RESULTS: After one melanoma cell line (1074mel) was found not to express functional β(2)m by cytofluorometric analysis, four (31%) of the 13 newly established melanoma cell lines were found to have an absolute lack of functional MHC class I expression. Northern blot analysis of RNA extracted from the five cell lines exhibiting no functional MHC class I expression showed that these cells contained normal levels of α-chain mRNA but variable levels of β(2)m mRNA. In addition, no immunoreactive β(2)m protein was detected by western blot analysis. When human β(2)m was transiently expressed with the use of a recombinant vaccinia virus, cell-surface MHC class I expression was reconstituted and the ability of these five cell lines to present endogenous antigens was restored. Immunohistochemical staining of tumor sections revealed a lack of immunoreactive MHC class I in vivo, supporting the notion that the in vitro observations were not artifactual. Furthermore, archival tumor sections obtained from patients prior to immunotherapy were available from three patients and were found to be β(2)m positive. This result was consistent with the hypothesis that loss of β(2)m resulted from immunotherapy. CONCLUSIONS: These data suggest that the loss of β(2)m may be a mechanism whereby tumor cells can acquire immunoresistance. This study represents the first characterization of a molecular route of escape of tumors from immune recognition in a cohort of patients being treated with immunotherapy.